SISTEM INFORMASI PENGAJUAN KLAIM PESERTA JAMINAN KESEHATAN (JKN) BERBASIS WEB DI RUMAH SAKIT Dr. M.M. DUNDA LIMBOTO - Lasena, Marlin (JSAI (Journal Scientific and Applied Informatics), 2020)
Changes in technology currently affect all aspects including health, to increase effectiveness and efficiency in the service, it is necessary to change to the old system to facilitate the patient and the parties Health service Provider in conducting health service process. Everyone has the right to live prosperous lives, reside, and gain a good and healthy environment and deserve health care "and" everyone has the right to social security that allows the development of himself. Wholly as a beneficial human being "this research uses Research and Development methods where the application is designed using programming language software Android, PHP, and HTML. The results concluded that by the existence of an information system of the claim submission of health care participants, the party hospital Dr. MM. Dunda Limboto can manage the file administration data of the claims of patients with more efficiently